Empowering Farmers Through a Practical and Energy-Efficient Goat Feed Chopping Machine - Dalil, M; Arief, Dodi Sofyan; Jahrizal, Jahrizal; Junaedi, Achmad Tavip; Susanti, Wilda; Tendra, Gusrio; Renaldo, Nicholas; Koto, Jaswar; Musa, Sulaiman; Wahid, Nabila; Cecilia, Cecilia (International Conference on Business Management and Accounting, 2024)
This initiative is part of a broader commitment to support rural agricultural development through technological innovation and knowledge transfer. Through workshops, demonstrations, and direct community involvement, this program will not only provide access to the feed chopper but also equip farmers with the skills and understanding needed to adopt and sustain its use. This community service project was designed using a participatory and problem-solving approach, integrating technical innovation with local knowledge to empower goat farmers. This community service initiative successfully introduced a practical and energy-efficient goat feed chopping machine to a rural farming community. The machine effectively addressed key challenges in manual feed preparation, including time consumption, labor intensity, and inconsistency in feed size. This initiative demonstrates that small-scale engineering solutions, when aligned with local needs and capacities, can significantly advance rural development and agricultural sustainability.